Omega-3 and Renal Function in Older Adults - Lauretani, F. (2009)
Chronic kidney disease (CKD) is a major public health problem and can result in end-stage renal disease with need for dialysis or transplantation. In Europe up to 12% of the adult population had some renal impairment, while in the United States the end stage of CKD has increased dramatically from 209.000 in 1991 to 472.000 in 2004. Diabetes and hypertension are major causes of kidney pathology. Infection, particularly ascending infection, is more common with increasing age, as both immune function declines and associated pathology predisposing to infection, such as obstructive uropathy, becomes more common. Most pathological changes in the kidney appear to be initiated by oxidative stress, followed by an inflammatory reaction. Oxidative stress results from an imbalance between free radicals and their detoxification by endogenous and exogenous scavengers, including polyunsatured fatty acids (PUFA). Recent studies showed that PUFA supplementation slowed the rate of loss of renal function in patients with IgA nephropathy. Then, studies of omega-3 supplementation in dialysis patients describe salutary effects on triglyceride levels and dialysis access patency. We examined the relationship between total plasma PUFA levels and change in creatinine clearance over a three-year follow-up in the older persons enrolled in the InCHIANTI study, a population-based epidemiology study conducted in Tuscany, Italy. This study showed that older adults with low total plasma PUFA levels have a greater decline in creatinine clearance over three years of follow-up. These findings suggest that a higher dietary intake of PUFA may be protective against progression to chronic kidney disease.